Amplification of mast cell density in oral squamous cell carcinoma and normal oral mucosa: A comparative study - Arpita Kabiraj; Vishal; Shantala R Naik; Prashant Gupta; Tanya Khaitan; Jaydeep Samanta (Wolters Kluwer Medknow Publications, 2023)
Background: Mast cells are thought to be complex, multifaceted cells that are important for tumor angiogenesis and immunopathology. Mast cell buildup at the periphery of the tumor and their production of strong pro- and angiogenic chemicals may be signs of a tumor-host interaction that encourages tumor evolution. As a result, the current study's objective was to evaluate mast cell density (MCD) in oral squamous cell carcinoma (OSCC) and healthy oral mucosa and to suggest their likely contribution to the growth and spread of the tumor. Methods: Ten cases of normal oral mucosa tissues and thirty OSCC patients with histological diagnoses of OSCC were both included in the research. Mast cell granules were examined on the slides under 10X and 40X magnification after being stained with 1% Toluidine blue. Results: The mean MCD was found to be greater in OSCC (83.59 ± 40.67) as compared to normal oral mucosa (30.26 ± 25.47). Conclusion: Assessment of mast cells in OSCC may serve as an angiogenesis promoter and the MCD appears to be a reliable prognostic marker with which patients at risk for recurrences can be identified.